Фраземіка Пантелеймона Куліша в «Cловарі української мови» за редакцією Бориса Грінченка - Устенко, Л. (Лексикографічний бюлетень, 2012)
Phraseological units from different styles and different genres in Panteleymon Kylish’s texts which are fixed in «Ukrainian Dictionary» published by Borys Grinchenko were analysed in the article. Analysis of idioms interpretation in different lexicographical codes was held. Not the same ways of explanation of phraseological units which are accompanied by illustrations from Kulish’s writings were stressed.